Exposure-adjusted road fatality rates for cycling and walking in European countries - Alberto Castro; Sonja Kahlmeier; Thomas Gotschi (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2018)
This paper presents fatality rates for walking and cycling in European Countries used in the World Health Organization's Health Economic Assessment Tool (HEAT). It evaluates and ranks the quality of data sources and gives fatality rates adjusted by exposure (i.e. distance travelled). It also discusses the different methodologies applied for national exposure data, as well as the proposed solutions to make these figures comparable across countries.
Keywords: 330